Investigation of the influence of loading histories on the ductility of RC linear members - Qureshi, Juneid; Ueda, Tamon; Karasudhi, Pisidhi; The Government of Norway (Bangkok : Asian Institute of Technology, 1990)
The development and application of a mathematical model , based on damage assessment, to predict ductility for a cantilever type of RC member has been established in this study. A ductility index, which effectively represents ductile behavior of a RC member, has been selected and termed as limiting ductility fac tor. The formulated model can be u sed to calculate the limiting ductility factor, and the corresponding number of cycles to reach it, for a member having any given set of material and specimen properties, when subjected to any form of cyclic loading history. Experimental confirmation of model results has been obtained by testing eleven doubly reinforced cantilever beams, having two different levels of shear stress, by subjecting them to different types of cyclic static loading histories , which include monoton ic , asymmetric and symmetric loadings with full and half rever sals of displacement. The model results have also been used for comparison with all previously available experimental data on cyclic loading and shows good agreement . The analysis of experimental results show that loading history has significant effect on ductility and that damage progression of a member is unique i.e independent of loading direction. Also it is seen that member behavior is closely linked with level of shear stress experienced. Based on observed results recommendation is made for the type of loading history that should be considered for determining ductility under typical earthquake loading.
A thesis submitted in partial fulfillments of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1990
Keywords: Reinforced concrete -- Ductility; Materials -- Dynamic testing